Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.17576/geo-2020-1602-18
|View full text |Cite
|
Sign up to set email alerts
|

Trust motivates funders to participate in Shari’ah crowdfunding

Abstract: The fourth industrial revolution has influenced many sector including Islamic Finance. The digital revolution has changed the traditional crowdfunding through the usage of technology with smart applications on mobile phones and websites. Among the advantage of crowdfunding is its accessibility, fast transaction, security, transparency, traceability and many more. Through crowdfunding platforms, financial inclusion groups could be reached. Hence, the demand for Shari'ah crowdfunding increases to fulfil the Musl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Ja'afar, (2022), and Mahfudz (2022) examine the social implications of Islamic finance and explores the concept of zakat, sadaqah, and waqf as mechanisms for promoting social inclusivity. This work provides a useful framework for understanding the social objectives of Islamic Fintech organizations as coined in the work of Nor and Hashim, (2020); Razak, Dali, Dhillon, and Manaf, (2021).…”
Section: 3mentioning
confidence: 99%
“…Ja'afar, (2022), and Mahfudz (2022) examine the social implications of Islamic finance and explores the concept of zakat, sadaqah, and waqf as mechanisms for promoting social inclusivity. This work provides a useful framework for understanding the social objectives of Islamic Fintech organizations as coined in the work of Nor and Hashim, (2020); Razak, Dali, Dhillon, and Manaf, (2021).…”
Section: 3mentioning
confidence: 99%
“…Research has shown that trust has a positive correlation with the amount of funding raised, particularly for campaigns with lower funding goals (Zheng et al, 2017). Nor & Hashim (2020) demonstrated that trust has a favourable impact on the amount of money contributed to social crowdfunding initiatives in Malaysia. Contributors are more likely to donate when they have confidence in the campaign organisers and believe that their donations will be used for specific purposes.…”
Section: Trustmentioning
confidence: 99%
“…Trust is a particularly critical factor when using fintech; after a customer has tried fintech, their continued use depends on building trust (Jena, 2022). According to Nor and Hashim (2020), fintech has influenced conventional crowdfunding using the internet and smartphone applications. On the one hand, platforms have raised funds for different activities, including social initiatives and entrepreneurship, and on the other hand, trust has become a concern that has deterred funders from online platform investment.…”
Section: Trust (Tr)mentioning
confidence: 99%